Návrh nových obchodních aktivit ve firmě Lipan A.EURO, a.s - Kovárník, František (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Cílem této práce je vytvořit návrh nových obchodních aktivit pro firmu Lipan A.Euro,a.s., která působí v oblasti prodeje a servisu automobilů. Práce řeší současný problém firmy, kdy nedokáže využít plně vlastních kapacit a hledá možnosti v poskytování doplňkových služeb. Projekt zohledňuje aktuální požadované trendy zákazníků. Návrhy jsou popsány z funkčního i technického hlediska, včetně možnosti způsobu realizace. U návrhů je rovněž provedena kalkulace finančních nákladů a zpracován finanční plán návratnosti nových projektů.

An aim of this work is to create a project of new business activities for a company Lipan A. Euro, a.s., that functions in sphere of car sale and car repair servise. The work solves present problem of company, which can not use own capacity wholly and searches some possibilities in additional servise. The project takes into account the customers actual required trends. The project is described from working point of view and technical aspect as well, including the possibilities of a way of their implementation. Next to the projects is made a calculation of financial costs and it is processed a financial plan of return on new projects.
Project of the new business activities in the company Lipan A.EURO, a.s
Keywords: nové obchodní aktivity; řízení lidských zdrojů; realizace projektu; new business activities; operating of human sources; implementation of project